Meritocracy Implementation Of The State Civil Servants As An Embodiment Of The Values Of Integrity And National Defensen Through A Public Ethics Perspective - Rasona Sunara; Atsil Syah Gibran; Andi Fiqih Abdan Irfandy; Fahrezy Gilang Dwi; Jhosalez Dea Delvia (PT Publikasiku Academic Solution, 2024)
This research aims to examine the implementation of the meritocracy principle in the Civil Servant Apparatus (ASN) employment system as an effort to strengthen the values of integrity and national spirit through the perspective of public ethics. Meritocracy is a concept that prioritizes assessment based on qualifications, performance, and individual achievements, rather than on political connections or nepotism. In the context of the ASN, the meritocratic system seeks to ensure that promotions, appointments, and rewards are given to individuals based on the achievements and competencies they have demonstrated. The implementation of the meritocracy system is expected to encourage ASN members to continuously improve the quality of the public services they provide. By considering performance and competency factors, it is hoped that ASN members will be more motivated to enhance their abilities and knowledge. This is also expected to reduce the practices of corruption and nepotism that often occur in non-meritocratic-based employment systems. This research will also analyze the challenges and obstacles that may arise in implementing a meritocratic system in ASN employment. Factors such as cultural resistance and policy sustainability will be the main focus of this analysis. Additionally, this research will discuss strategies and recommendations to overcome these challenges and strengthen the implementation of the meritocracy system.